Human-centered design approaches in health sciences research - Subedi, Madhusudan (Journal of Patan Academy of Health Sciences, 2025)
IntroductionIn the rapidly evolving field of health sciences, traditional paradigms of research and innovation are being challenged by a growing recognition of the need for more inclusive, empathetic, and context-sensitive approaches. Human-Centered Research Design(HCRD) has emerged as a transformative methodology that prioritizes the lived experiences, beliefs and values, socio-economic and religious contexts, and needs of individuals and communities into the core of health research and innovation. HCRD is recognized for addressing complex social challenges related to health, development, and well-being. This editorial highlights the principles, applications, benefits, and challenges of HCRD in health sciences, arguing for its central role in shaping equitable and impactful health interventions.Principles of human-centered research designHCRD can be broadly conceptualized as a methodological framework that integrates iterative cycles of divergent and convergent thinking. Through these alternating modes of exploration and synthesis, the process seeks to harness the benefits of addressing complex challenges and generating solutions from a human-oriented perspective. At its core, this approach emphasizes the prioritization of human needs, experiences, and values, while simultaneously negotiating the constraints imposed by practical, technological, and organizational realities. HCRD focuses on engaging end-users to understand their needs, behaviors, values, and preferences to create products, services or systems that are effective, efficient, and enjoyable.By balancing empathy-driven inquiry with feasibility considerations, HCRD facilitates the creation of solutions that are not only innovative but also contextually viable, socially acceptable and sustainable. Thus, the essence of HCRD lies in understanding the emotional, social, and cultural dimensions of health experiences.